KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU BUDAYA PENDIDIKAN SISWA - Syamsul Falah, Moh (Universitas Negeri Surabaya, 2023)
Abstract : The principal as an institutional leader has become his duty to be able to organize and manage educational institutions properly. Especially in improving the quality of the culture that will be built. Therefore, school principals are required to be creative and active in being involved in it so that they can change in improving the quality of school culture. The quality of student education culture in question is the quality of a religious education culture, namely the quality of culture that leads to a prophetic culture. This research methodology uses a naturalistic qualitative approach by developing existing data through data collection techniques of observation, interviews, and documentation. Then the data were analyzed with data reduction techniques, data display, verification, and conclusions. The results showed that the principal in improving the quality of Student Education Culture was carried out in various ways. First, school institutions involve parents as institutional partners by holding nabawi parenting activities. Second, the daily monitoring book which is brought home by students every day then filled in by parents and returned to school. Keywords: leadership; quality culture; student education Abstrak: Kepala sekolah selaku pemimpin kelembagaan sudah menjadi tugasnya untuk dapat mengatur dan mengelola lembaga pendidikan dengan baik. Apalagi dalam meningkatkan kualitas budaya yang akan dibangunnya. Oleh sebab itu, kepala sekolah dituntut untuk kreatif dan aktif dalam terlibat di dalammnya supaya dapat merubah dalam meningkatkan mutu budaya sekolah. Mutu Budaya Pendidikan siswa yang dimaksud adalah mutu budaya pendidikan yang religius yakni mutu budaya yang mengarah pada budaya kenabian. Metodologi penelitian ini menggunakan pendekatan kualitatif naturalistic dengan mengembangkan data yang ada melalui tehnik pengumpulan data observasi, interview, dan dokumentasi. Lalu data dianalisis dengan tehnik reduksi data, display data, verifikasi, dan kesimpulan. Hasil penelitian menunjukkan bahwa kepala sekolah dalam meningkatkan mutu Budaya Pendidikan Siswa dilakukan dengan berbagai cara. Pertama, Lembaga sekolah melibatkan orang tua sebagai partner kelembagaan dengan mengadakan kegiatan parenting nabawi. Kedua, buku monitoring harian yang setiap hari dibawa pulang oleh siswa lalu diisi orang tua dan dikembalikan ke sekolah. Kata Kunci: kepemimpinan; budaya mutu; pendidikan siswa